Topiramate and severe metabolic acidosis: case report Acidose metabólica grave por topiramato: relato de caso - Jayme E. Burmeister; Rafael R. Pereira; Elisa M. Hartke; Michele Kreuz (Arquivos de Neuro-Psiquiatria)
Topiramate infrequently induces anion gap metabolic acidosis through carbonic anhydrase inhibition on the distal tubule of the nephron - a type 2 renal tubular acidosis. We report on a 40 years old woman previously healthy that developed significant asymptomatic metabolic acidosis during topiramate therapy at a dosage of 100mg/day for three months. Stopping medication was followed by normalization of the acid-base status within five weeks. This infrequent side effect appears unpredictable and should be given careful attention. Topiramato pode produzir raramente uma acidose metabólica através da inibição da anidrase carbônica no túbulo distal do néfron - acidose tubular renal do tipo 2. Relatamos o caso de mulher de 40 anos previamente saudável que desenvolveu quadro de acidose metabólica assintomática grave, sem outra etiologia identificável, durante uso de topiramato na dose de 100mg/dia por três meses. Este efeito colateral, embora infrequente, parece ser imprevisível e requer atenção cuidadosa.